2000
DOI: 10.1038/sj.leu.2401705
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor NF-κB is constitutively activated in acute lymphoblastic leukemia cells

Abstract: The pleiotropic transcription factor NF-B controls cellular apoptotic and growth processes and increasing evidence suggests a role in tumorigenesis. We describe here that constitutively activated NF-B complexes are found in the vast majority (39 out of 42 samples) of childhood acute lymphoblastic leukemia (ALL) without any subtype restriction. Electrophoretic shift analysis further demonstrates that these complexes are composed of p50-p50 and p65-p50 dimers. Proteasome inhibition in primary ALL cultures result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(167 citation statements)
references
References 23 publications
10
155
0
2
Order By: Relevance
“…Consistent with this, NF-kB activation is detected in the bone marrow of patients with myelodysplastic syndrome (Braun et al, 2006), which is considered a precursor disease of AML. NF-kB is also activated in childhood acute lymphoblastic leukemia (Kordes et al, 2000), Hodgkin-Reed-Sternberg cells (Bargou et al, 1997), HTLV-1-positive leukemias (Hiscott et al, 2006), B-cell chronic lymphocytic leukemia (Furman et al, 2000;Zaninoni et al, 2003) and in primary blasts of CML (Kirchner et al, 2003). In addition, NF-kB-dependent gene transcription is a hallmark of the activated B-cell-like subset of diffuse large B-cell leukemia (Lam et al, 2005;Ngo et al, 2006).…”
Section: Nf-kb In Hematologic Malignanciesmentioning
confidence: 99%
“…Consistent with this, NF-kB activation is detected in the bone marrow of patients with myelodysplastic syndrome (Braun et al, 2006), which is considered a precursor disease of AML. NF-kB is also activated in childhood acute lymphoblastic leukemia (Kordes et al, 2000), Hodgkin-Reed-Sternberg cells (Bargou et al, 1997), HTLV-1-positive leukemias (Hiscott et al, 2006), B-cell chronic lymphocytic leukemia (Furman et al, 2000;Zaninoni et al, 2003) and in primary blasts of CML (Kirchner et al, 2003). In addition, NF-kB-dependent gene transcription is a hallmark of the activated B-cell-like subset of diffuse large B-cell leukemia (Lam et al, 2005;Ngo et al, 2006).…”
Section: Nf-kb In Hematologic Malignanciesmentioning
confidence: 99%
“…A few examples include classical Hodgkin's lymphoma (cHL), multiple myeloma (MM), primary mediastinal B-cell lymphoma (PMBL), therapy-resistant diffuse large B-cell lymphoma (DLBCL), childhood acute lymphoblastic leukemia (c-ALL) and breast, prostate, ovarian, lung, colon and renal cell carcinoma (Bargou et al, 1997;Nakshatri et al, 1997;Sovak et al, 1997;Alizadeh et al, 2000;Cogswell et al, 2000;Kordes et al, 2000;Davis et al, 2001;Hinz et al, 2001;Kalaitzidis et al, 2002;Shipp et al, 2002;Munzert et al, 2004). Accumulating evidence suggests that NF-kB also contributes to brain cancer, as a novel trkAIII splice variant of the neurotrophin tyrosine kinase receptor type 1 (TrkA) was shown to oppose growth-restricting nerve growth factor (NGF)/TrkAI signaling in neuroblastoma and to stimulate tumor-promoting signaling via PI3K/Akt and NF-kB (Tacconelli et al, 2004).…”
Section: Update On Nf-jb's Protective Activity Following Viral Infectmentioning
confidence: 99%
“…This is best exemplified by the fact that expression of a super-repressor IkBa mutant noticeably sensitizes many tumor-derived cells to chemotherapy and induces apoptosis (reviewed in Baldwin, 2001;Kucharczak et al, 2003;Lin and Karin, 2003). In many cases, NF-kB is persistently activated in tumors owing to constitutive IKK kinase activity, but there are several examples where it results from overexpression and nuclear accumulation of the c-Rel protein (Bargou et al, 1997;Nakshatri et al, 1997;Sovak et al, 1997;reviewed in Rayet and Ge´linas, 1999;Alizadeh et al, 2000;Cogswell et al, 2000;Kordes et al, 2000;Davis et al, 2001;Hinz et al, 2001;Gilmore et al, 2002;Kalaitzidis et al, 2002;Karin and Lin, 2002;Shipp et al, 2002;Barth et al, 2003;Munzert et al, 2004;Feuerhake et al, 2005;Fan et al, 2006a, b). Recent work from Lou Staudt's group has shown that caspase recruitment domain family member 11 (CARD11)/card-membrane-associated guanylate kinase (MAGUK) protein 1 (CARMA1) drives constitutive activation of the IKK complex via MALT1 and B-cell lymphoma 10 (BCL-10) in therapy-resistant diffuse large B cell lymphoma (DLBCL) (Ngo et al, 2006).…”
Section: Update On Nf-jb's Protective Activity Following Viral Infectmentioning
confidence: 99%
“…Moreover, T-ALL cell lines present constitutively phosphorylated forms of Akt independently of external growth factors (20). In addition, NF-κB, a downstream target of PI3K/Akt, is constitutively activated in some primary T-ALL samples (24). Nevertheless, no activating mutations of PI3K and/or Akt have been described in T-ALL.…”
Section: Pi3k/aktmentioning
confidence: 99%